Developments in the Chemical Synthesis of Heparin and Heparan Sulfate. Issue 11 (15th September 2021) - Pongener, Imlirenla; O'Shea, Conor; Wootton, Hannah; Watkinson, Michael; Miller, Gavin J.
Abstract: Heparin and heparan sulfate represent key members of the glycosaminoglycan family of carbohydrates and underpin considerable repertoires of biological importance. As such, their efficiency of synthesis represents a key requirement, to further understand and exploit the H/HS structure‐to‐biological function axis. In this review we focus on chemical approaches to and methodology improvements for the synthesis of these essential sugars (from 2015 onwards). We first consider advances in accessing the heparin‐derived pentasaccharide anticoagulant fondaparinux. This is followed by heparan sulfate targets, including key building block synthesis, oligosaccharide construction and chemical sulfation techniques. We end with a consideration of technological improvements to traditional, solution‐phase synthesis approaches that are increasingly being utilised. Abstract : This review describes recent advances (2015 onwards) surrounding the chemical synthesis of heparin and heparan sulfate.